HUBUNGAN PENGETAHUAN SIKAP DAN PERILAKU MASYARAKAT DALAM MELAKSANAKAN 4M PLUS DENGAN KEJADIAN DBD DI DESA UBUNG KAJA KECAMATAN DENPASAR UTARA TAHUN 2021 - I Gede Jepri Suantara; Ni Ketut Rusminingsih; Anysiah Elly Yulianti (Poltekkes Kemenkes Denpasar, 2022)
AbstractDengue Hemorrhagic Fever is a disease caused by dengue virus infection which is still a public health problem. This disease is found in almost all parts of the world, especially in tropical and subtropical countries, both as an endemic and epidemic disease. In 2017, the highest number of dengue cases in Bali was in Denpasar, with 929 cases with 4 deaths. The purpose of this study was to determine the relationship between the knowledge of attitudes and behavior of the community in implementing 4M Plus with the incidence of dengue fever in the village of Ubung Kaja. This type of research is descriptive with the case control method. The sampling technique used total sampling. The number of samples is 78 respondents with 39 case samples and 39 control samples. The data analysis technique used the chi-square test with a significance level (p = 0.05) and odd ratios were used to determine the risk. The variables proven to be related to the implementation of 4M Plus and the incidence of dengue fever in the village of Ubung Kaja were knowledge p = 0.000 (OR =7,933 ), attitude p = 0.001 (OR =8,313 ) and behavior p = 0.000 (OR =8,800 ). The conclusion is that there is a relationship between the level of knowledge, attitudes and behavior of the community in implementing 4M Plus with the incidence of dengue fever in the village of Ubung Kaja. Suggestions that can be conveyed are the community to optimize clean and healthy living habits, especially in terms of eradicating mosquito nests with 4M Plus to avoid dengue disease.Keywords: knowledge, attitudes, behavior, 4M Plus, DHF